Application of The Make A Match Cooperative Learning Model to Improve Student Learning Outcomes on The Circulatory System Topic - Mohammad Liwa Ilhamdi; Agil Al Idrus; Ahmad Reza Mahendra; Mega Nofitri Ikhwan (MO.RI Publishing, 2026)
This study is a classroom action research (CAR) aimed at improving student learning outcomes on the circulatory system topic through the application of the Make A Match cooperative learning model. The study was conducted at SMA Negeri 5 Mataram with Grade XI students as research subjects. It was carried out in two cycles, each comprising the stages of planning, action implementation, observation, and reflection. The research data covered the implementation of learning using the Make A Match model and student learning outcomes. Data were collected through teacher and student activity observation sheets and learning outcome tests in the form of quizzes and written assignments. Data analysis was conducted descriptively to describe improvements in the learning process and outcomes across each cycle. The results indicated that the application of the Make A Match cooperative learning model was effective in enhancing student learning activity and improving learning outcomes on the circulatory system topic. Therefore, the Make A Match model can be recommended as an alternative biology learning method to support active and meaningful learning.